MOBILISASI SDM DALAM PENGEMBANGAN PENGUSAHA KECIL DI KECAMATAN WORI KABUPATEN MINAHASA UTARA - Tumengkol, Selvie (JURNAL ADMINISTRASI BISNIS, 2014)
Small trademen development which one of model to force economic growth of Indonesia. The experiment to show how for human resources mobilisation cant improve business development for small trademan. The experiment conducted Wori district using 6 village from 18 village or Wori district. Using 20 respondents every village. The result research showed that to force improving small traders can be used human resources mobilisation.